Upregulation of Neurotrophic Factors Selectively in Frontal Cortex in Response to Olfactory Discrimination Learning. (30th May 2007) - Naimark, Ari; Barkai, Edi; Matar, Michael A.; Kaplan, Zeev; Kozlovsky, Nitzan; Cohen, Hagit
Abstract : We have previously shown that olfactory discrimination learning is accompanied by several forms of long-term enhancement in synaptic connections between layer II pyramidal neurons selectively in the piriform cortex. This study sought to examine whether the previously demonstrated olfactory-learning-task-induced modifications are preceded by suitable changes in the expression of mRNA for neurotrophic factors and in which brain areas this occurs. Rats were trained to discriminate positive cues in pair of odors for a water reward. The relationship between the learning task and local levels of mRNA for brain-derived neurotrophic factor, tyrosine kinase B, nerve growth factor, and neurotrophin-3 in the frontal cortex, hippocampal subregions, and other regions were assessed 24 hours post olfactory learning. The olfactory discrimination learning activated production of endogenous neurotrophic factors and induced their signal transduction in the frontal cortex, but not in other brain areas. These findings suggest that different brain areas may be preferentially involved in different learning/memory tasks.